Aplikasi Konsep Model Teori Menurut Sister Calista Roy Pada Asuhan Keperawatan Diabetes Melitus Diruangan Rawat Inap - Munawaroh Meihati; Nursanti Irna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The application of nursing care is in accordance with the nursing model with Sister Calista Roy with cases of Diabetes Mellitus in the inpatient room. The aim of this research is to provide nursing care to Mr. N with Diabetes Mellitus based on Sister Calista Roy's theory. This research method is a case study with a nursing care approach based on Sister Calista Roy's theory. Data collection was carried out by means of interviews, observations, physical examinations and documentation studies. The instrument used is an assessment format based on Sister Calista Roy's nursing theory. Results of the study Wounds that did not heal after amputation of the thumb and index toe of the left foot for approximately 4 weeks. The first wound was found between the big toe and forefinger approximately 4 months ago. The wound does not heal and slowly gets bigger and festers around the wound area. The first time he consulted at the Regional Hospital, he was then referred to Hospital P, where he was treated for 1 month. During his treatment at the hospital, his thumb and forefinger were amputated. But the surgical wound turned non-healing with pus and black color. So the doctor suggested a below-the-knee amputation. He underwent leg amputation surgery 3 weeks earlier. There are two nursing problems, namely damage to skin integrity and physical mobility. The interventions carried out are based on SLKI and SIKI. After providing nursing care for three days, it was concluded that two nursing problems had been partially resolved. It is hoped that nurses will be able to provide and improve the quality of service in providing nursing care based on the Sister Calista Roy approach.